2014
DOI: 10.1007/s00464-014-3880-4
|View full text |Cite
|
Sign up to set email alerts
|

Long-term symptoms, quality of life, and fertility after colorectal resection for endometriosis: extended analysis of a randomized controlled trial comparing laparoscopically assisted to open surgery

Abstract: Symptoms and QOL improvements after colorectal resection last for over 4 years without difference between the routes. Thank to a lower intra- and postoperative complications and higher spontaneous pregnancy rate, laparoscopic colorectal resection should be the first surgical approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 32 publications
2
25
0
2
Order By: Relevance
“…Nineteen studies were prospective in nature [24,27,29,30,32,37,38,[40][41][42][43][44][48][49][50]52,55,56,59], 2 were randomized controlled trials (one of which was an extended analysis of a randomized controlled trial) [20,28], and 20 were retrospective studies [11,21− (Table 1) [11,20−59]. The mean follow-up period ranged between 12 and 108 months.…”
Section: Study Characteristics: Descriptive Analysismentioning
confidence: 99%
“…Nineteen studies were prospective in nature [24,27,29,30,32,37,38,[40][41][42][43][44][48][49][50]52,55,56,59], 2 were randomized controlled trials (one of which was an extended analysis of a randomized controlled trial) [20,28], and 20 were retrospective studies [11,21− (Table 1) [11,20−59]. The mean follow-up period ranged between 12 and 108 months.…”
Section: Study Characteristics: Descriptive Analysismentioning
confidence: 99%
“…A large prospective study of over 200 women having surgery with or without bowel resection for severe endometriosis shows a cumulative live birth rate of 36%, 50% and 67% at 1, 2 and 3 years post‐index surgery, with no difference whether bowel resection was undertaken or not, with half achieving pregnancy with expectant management and the remainder with assisted reproductive technology . Similar outcomes are reported from a French team performing open or laparoscopic bowel resection, where cumulative pregnancy rates following surgery were 60% with a median of 19 months follow‐up although it was reported in an extended analysis from the same group that pregnancy after expectant management only occurred in the laparoscopy group . In the most recent series of 111 women having bowel resection for deeply invasive disease, 73% of women were pregnant at 12 months of follow‐up with the majority after expectant management .…”
Section: Deeply Invasive Endometriosis Bowel Resection and Fertilitymentioning
confidence: 53%
“…This study demonstrated that laparoscopy can provide patients with a higher pregnancy rate. Touboul, Cyril [29] also believe that laparoscopy can improve postoperative pregnancy rate of patients, but most patients have a successful pregnancy within 2 years after surgery. Many professors believe that surgery combined with ART can be the rst choice for patients.…”
Section: Discussionmentioning
confidence: 99%